Study of Four Main Pillars of Quality Education in Mobile Learning Centres (Delhi) - REKHA, CHITER (THE PRIMARY TEACHER, 2015)
Mobile Learning Centres (MLCs) or Chalta Phirta School are being run by NonGovernment Organisations in Delhi. This is an initiative conceived and supported by Government of National Capital Territory of Delhi and the UEE (Universalisation of Elementary Education) Mission. It focuses on children who are out of school and ensures that they receive non-formal education and subsequently attend a regular school. This study was conducted to study the four main pillars i.e. (Instructors, professional qualifications and their teaching competencies, Teaching Learning Material (TLM) & Teaching Learning Process (TLP) of quality education in Mobile Learning Centers. What extent the quality education is provided by the Mobile Learning Centres in accordance with their prescribed duties under Sarva Shiksha Abhiyan (SSA)? How far have they been successful? The sample comprised six Mobile Learning Centres, 12 Instructors and 180 children. Survey Method was adopted for the collection of data. The tools used for the study include interview schedule, observation schedule and check list. A qualitative approach was adopted to analyse and interpret the data using some quantification in form of percentag